Pelatihan Sikap Bertanggungjawab Anak Panti Asuhan Cahaya Kasih Sumber Sari Bandung - Agustinus Tanggu Daga; Wahyuning Dwi Wardani Ndraha; Maria Oktaviane (LPPM UNINUS, 2021)
One of the problems in the Cahaya Kasih orphanage is the lack of responsibility of the children at the orphanage. The purpose of this training activity is to develop a responsible attitude for the children of the Cahaya Kasih orphanage. The problem-solving method used is training through emotional freedom therapy, group sensitivity, reality therapy, and lectures on responsibility material. Participants' responses to this training were obtained through written answers collected at the end of each activity session.The results of this training show that the participants can help increase their knowledge and understanding of responsible attitudes, help them recognize and let go of negative emotions that hinder responsibility, help them identify the skills that support a responsible attitude, help them to realize their aspirations and the efforts that have been and will be made to achieve them. Based on these results, the authors conclude that responsible attitude training through emotional freedom therapy, group sensitivity, and reality therapy activities can increase knowledge and understanding and develop a responsible attitude for the children of the Cahaya Kasih orphanage in Bandung. Therefore, the authors suggest that training on emotional freedom therapy, group sensitivity, reality therapy can be applied to reduce negative behavior and develop a responsible attitude for orphanage children.